Treatment and outcome of patients with metastatic NSCLC: a retrospective institution analysis of 493 patients - Reinmuth, Niels; Payer, Nadine; Muley, Thomas; Hoffmann, Hans; Herth, Felix; Villalobos Bollen, Matthias Americo; Thomas, Michael (Respiratory research, 2013)
BACKGROUND: Most patients with metastatic non-small cell lung cancer (NSCLC) will face treatment with systemic therapy. Current clinical studies are demonstrating improvements in chemotherapy and overall survival. However, it remains unclear whether these results are translated into clinical practice. - METHODS: We reviewed all stage IV NSCLC patients without second malignancies that were diagnosed from 2004 to 2006 at our institution. 493 consecutive patients were included into this retrospective analysis and were followed-up until end of 2011. - RESULTS: 352 patients (71.4%) received systemic therapy for up to 7 lines. For most patients, adjustments of dosages or applications had to be made at some point of the treatment, but the total applied dose remained generally close to the intended dose. The best disease control (BDC) rate decreased with increasing therapy lines from 59.7% to about 35%. Patients with palliative local therapy but no systemic treatment demonstrated inferior survival (median 2.9 versus 8.7 months, p < 0.001). The median interval between last treatment and death was 50 days and 15 days for chemotherapy and anti-EGFR therapy, respectively. BDC to the previous therapy lines was predictive for improved BDC to third- but not second-line therapy. Performing multivariate analysis, BDC to previous therapy, never-/ former-smoking status, and age > 70 years were associated with improved survival performing third-line therapy. - CONCLUSIONS: Stage IV NSCLC patients may receive substantial systemic therapy resulting in response and median survival rates that are comparable to data from clinical studies. However, preselection factors are increasingly important to improve therapy outcome and life quality.
Gesehen am 07.01.2022
DOI funktioniert nicht